Internal Autobiographical Mapping and Behavioral Persistence: A Neuroscience-Informed Psychological Model (Journal of Advances and Scholarly Researches in Allied Education, 2026)
This paper introduces the Internal Autobiographical Map (IAM) as a structural psychological concept of explaining repetitive human behavioral patterns. It states that behavior is not largely motivated by conscious choice or external circumstances, but is more of well-founded internal processes established by autobiographical experience and especially at an early age. Such experiences are understood by people and slowly converted to inner beliefs, rules of behavior, and identity roles that determine perception, emotional reactions, and decisions throughout life. Based on the ideas of autobiographical memory theory, neuroscience of behavioral prediction, and psychological identity formation, the research clarifies how memory functions as a predictive system that strengthens the already familiar behavioral responses, despite them being maladaptive. The study emphasizes that habitual patterns are maintained by automatic mechanisms and emotional stimulation that is associated with previous experiences. It also highlights how structural awareness and restructuring of these internal structures would be necessary to bring about meaningful behavioral change as opposed to depending on motivation alone. IAM model offers a methodical manner of detecting these patterns and getting to know their cause hence a basis of long-term behavioral change and self-improvement.